2016
DOI: 10.1016/j.nlm.2016.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in learned fear expression and extinction involve altered gamma oscillations in medial prefrontal cortex

Abstract: Sex differences in learned fear expression and extinction involve the medial prefrontal cortex (mPFC). We recently demonstrated that enhanced learned fear expression during auditory fear extinction and its recall is linked to persistent theta activation in the prelimbic (PL) but not infralimbic (IL) cortex of female rats. Emerging evidence indicates that gamma oscillations in mPFC are also implicated in the expression and extinction of learned fear. Therefore we re-examined our in vivo electrophysiology data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
38
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 38 publications
5
38
2
Order By: Relevance
“…This includes fear extinction, which involves theta and gamma oscillations in mPFC 12,13 . We have shown in rats that enhanced learned fear expression and reduced extinction recall in females, compared to males, are accompanied by sex differences in these prefrontal oscillations 14,15 .…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…This includes fear extinction, which involves theta and gamma oscillations in mPFC 12,13 . We have shown in rats that enhanced learned fear expression and reduced extinction recall in females, compared to males, are accompanied by sex differences in these prefrontal oscillations 14,15 .…”
mentioning
confidence: 90%
“…After extended auditory fear discrimination training, we recorded local field potentials (LFPs) in mPFC during retrieval testing to determine if discrimination and generalization in males and females, respectively, are characterized by sex differences in mPFC function. The prelimbic (PL) and infralimbic (IL) subregions of mPFC play opposing roles in the expression and extinction of learned fear 4 and we have previously shown sex differences in theta (4-12 Hz) and low gamma (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) oscillations in these areas during learned fear expression and extinction 14,15 . As there is also evidence for distinct contributions of PL and IL to fear discrimination 29,36 , we recorded LFPs from both of these mPFC subregions at retrieval.…”
mentioning
confidence: 99%
“…Studies examining the neural mechanisms of development and maintenance of trauma-related psychopathology have focused mainly on circuits implicated in fear processing [1719], emotional regulation [20, 21], and stress response [22, 23], including cortical, limbic, and salience regions. Most commonly, these regions have included the amygdala, limbic and salience hub linked to emotional processing and response [24, 25], hippocampus, associated with learning and memory [26], insula, a major salience hub implicated in self-referential processing [20], and prefrontal cortex (PFC).…”
Section: Introductionmentioning
confidence: 99%
“…A handful of studies have directly compared animals of both sexes on tests of cued and contextual fear conditioning. Some of these reports have shown that while males and females exhibit equivalent levels of fear conditioning to discrete cues (Maren et al 1994;Baran et al 2009;Milad et al 2009a;Barker and Galea 2010;Gruene et al 2015a;Fenton et al 2016), males often show evidence of better contextual conditioning (Maren et al 1994;Chang et al 2009;Barker and Galea 2010). Other studies have tested for sex differences in fear extinction learning, a form of learning through which animals learn to inhibit responding to cues that once signaled an aversive event.…”
mentioning
confidence: 99%
“…Over the last several years, the study of fear extinction has received considerable attention (Milad and Quirk 2012) due in part to the fact that humans with PTSD display impaired extinction (Milad et al 2009b;Norrholm et al 2011). Recent findings in rodents are mixed with regard to sex differences in fear extinction with several studies reporting no difference between males and females (Milad et al 2009a;Rey et al 2014;Gruene et al 2015a), while others have found that females show weaker fear extinction (Baran et al 2009(Baran et al , 2010Matsuda et al 2015;Fenton et al 2016). Moreover, other studies have found that the retention of extinction learning in female rats varies depending on estrus stage such that rats exposed to extinction training while in proestrus show better retention of extinction (Milad et al 2009a;Rey et al 2014).…”
mentioning
confidence: 99%